Nanotechnology-driven coordination of shoot–root systems enhances rice nitrogen use efficiency - Chuanxi Wang; Bingxu Cheng; Zhenggao Xiao; Yahui Ji; Jiangshan Zhang; Rongxin Zhou; Xian-Zheng Yuan; Melanie Kah; Zhenyu Wang; Baoshan Xing (Proceedings of the National Academy of Sciences, 2025)
Enhancing nitrogen use efficiency (NUE) in agricultural production can reduce fertilizer input, mitigate greenhouse gas emissions and decrease water pollution incidence. However, improving NUE in farming systems without compromising food security remains challenging. Herein, we have successfully developed and applied selenium-based nanotechnology, which capitalizes on above- and belowground synergies to enhance field-scale NUE. Specifically, when N fertilizer application was reduced by 30%, foliar application of selenium nanomaterials significantly enhanced rice photosynthesis by 40.3% compared with reduced N fertilizer treatment (189 kg N/ha). This enhancement promoted carbohydrate synthesis and translocation, providing abundant carbon sources for rhizosphere processes. These abundant carbon sources modulated rhizosphere N transformation processes, stimulating ammonification and nitrification while suppressing denitrification, thereby reducing methane, ammonia, and nitrous oxide emissions by 18.8 to 45.6%. In addition, compared with controls (270 kg N/ha), our approach improved rice root growth and upregulated gene expression associated with N uptake and translocation, increasing rice NUE (48.3%). While maintaining comparable yields to conventional practice, we observed significant improvements in rice quality parameters including crude protein, amino acids, and Se content. Furthermore, the application of this above- and belowground synergistic nano-regulation technology reduced environmental negative impacts by 41.0% and increased economic benefits by 38.2% per ton of rice produced, relative to conventional practices. This work elucidates how nano-enabled agricultural regulation achieves reduced input, enhanced efficiency, and increased income, emphasizing the high potential of nanotechnology in agricultural applications, particularly in improving the utilization efficiency of N fertilizers.